Socio-economic position and adolescents’ health in Italy: the role of selfesteem and self-efficacy (Italian Journal of Public Health, 2007)
Background: To underline the importance of self-esteem and self-efficacy as aspects of health promotion, we investigated the hypothesis that self-esteem and self-efficacy mediate the effect of socio-economic position on adolescents’ health. This association has been confirmed by our data.Methods: Data derive from the international Health Behaviours in School-aged Children (HBSC) study, 2001- 02 edition: a representative sample of Italian children (age groups of 11, 13 and 15years, N=4386) was administered a questionnaire at school. We tested with a multivariate model the effect of economic wellbeing on health and behavioural outcomes, first excluding, and then including, self-esteem and self-efficacy among the determinants.Results: Perceiving poorer health, not eating enough fruits and vegetables and doing too little physical activity are conditions affected by economic well-being (O.R. of best-off to worst-off are 0.65, 0.83 and 0.46, all statistically significant), while smoking habit is not affected. Including self-esteem and self-efficacy into the model significantly lowers, or annihilates, the effect of economic conditions on these outcomes.Conclusions: Economic well-being affects adolescents’ health (perceived health and health behaviours) in Italy, but it is reasonable to hypothesize that self-esteem and self-efficacy are among the mediators of this effect. Targeted interventions aimed at enhancing self-esteem and self-efficacy could therefore help in mitigating the effect of health inequalities.
Keywords: Self-esteem; self-efficacy; adolescence; socio-economic position; health